A eukaryotic transcriptional repressor with carboxypeptidase activity - GONG-PING HE; MUISE, A; WU LI, A; HYO-SUNG RO (Nature (London), 1995)
Adipocyte differentiation involves the transcriptional activation of several genes in triglyceride metabolism, including the adipose P2 (aP2 or 422) gene that encodes the adipocyte lipid-binding protein ALBP. Within the mouse aP2 promoter region, the AE-1 sequence functions as either a positive or a negative element in the regulation of aP2 gene expression. The AE-1 sequence is the binding site for the positive murine (3T3) adipocyte factor C/EBP-alpha, several human preadipocyte factors, and a 3T3 preadipocyte factor(s) that has been implicated as a repressor of aP2 gene expression. Here we report the cloning of new complementary DNAs that encode the 3T3 preadipocyte factor (termed AEBP1) and demonstrate that AEBP1 expression is abolished during adipocyte differentiation. Furthermore, we show that an activity of a carboxypeptidase associated with AEBP1 is important in the transcriptional repression function of AEBP1. Thus AEBP1 might represent a new type of transcription factor that regulates transcription by cleavage of factors involved in transcription.